Preliminary Investigation of Microdosimetric Track Structure Physics Models in Geant4-DNA and RITRACKS. (1st June 2015) - Douglass, Michael; Penfold, Scott; Bezak, Eva
Abstract : The major differences between the physics models in Geant4-DNA and RITRACKS Monte Carlo packages are investigated. Proton and electron ionisation interactions and electron excitation interactions in water are investigated in the current work. While these packages use similar semiempirical physics models for inelastic cross-sections, the implementation of these models is demonstrated to be significantly different. This is demonstrated in a simple Monte Carlo simulation designed to identify differences in interaction cross-sections.